Analysis of Crude Oil Price Determinants on Indonesia's Export Volume for the Period 1992 -2022 - Fibria Anggraini Puji Lestari (Ilomata International Journal of Social Science, 2023)
This study was motivated by curiosity about the impact of world oil prices on the economy in Indonesia. The study was conducted in Indonesia and used secondary data from relevant agencies. The analytical technique used is multiple linear regression with time series data from 1992 to 2022. The results show simultaneous production variables, worldwide oil prices, growth, and exchange rates. have the same effect on export volumes. However, part of the production variable has a positive and significant impact, the world oil price variable has a positive but insignificant effect, the economic growth variable has a positive and significant impact, the exchange rate variable has a negative impact and insignificant to the volume of Indonesia's crude oil exports.